A Review on Block Chain Technology (International Journal of Innovative Research in Computer Science & Technology, 2021)
Block chain is the foundation of all  cryptocurrencies, including Bitcoins. Without the need of  a third-party media, Blockchain is utilized for bitcoin  transactions all around the world. Blockchain is used for  worldwide decentralized transactions in the same manner  that the internet is used for global decentralized  communication. It aids in the protection of both the  provider and the customer from third-party participation,  the establishment of a tolerance network, the prevention  of data tampering, and the lowering of operating  expenses. It was first invented in 1991 and reintroduced  to the world in 2008 by Satoshi Nakamoto, and now, with  Blockchain 2.0, it is expected to be used not only in  cryptocurrency but also in the electronic industry,  including supply chain management, electronics  manufacturing, and power and energy systems.  Blockchain is a new kind of information technology that  has the potential to transform technology, business, and  commerce by making it more transparent, secure, and  dependable. The decentralized record-keeping potential  of block-chain is unlimited. This technology may be used  in a variety of applications in the future, from increased  user privacy and security to cheaper processing costs and  fewer mistakes owing to less human involvement.
Keywords: Block-chain; Supply Chain Management; Crypto currency